Handwriting automaticity: the search for performance thresholds - Medwell, Jane; Wray, David (Taylor & Francis, 2013)
Although handwriting has a fairly low status in literacy education, evidence is accumulating that it has an important role in written composition. In particular, handwriting automaticity appears to relate to success in composition. This relationship has been little explored in British contexts and we currently have little idea of what threshold performance levels might be. In this paper we report on two linked studies which attempted to identify performance levels in handwriting automaticity for children at two ages, below which their success in writing composition might be considered to be at risk. We conclude by suggesting interpolated levels for children at different ages, although we recognise the tentative nature of these suggestions.